Hubungan Antara Lama Hemodialisis Dengan Kualitas Hidup Pada Pasien Penyakit Ginjal Kronik (Pgk) Stadium 5 Di RSUD RAA Soewondo Pati - Nurhidayati, Septi, Dr. Suryo Aribowo Taroeno, M.Kes., Sp.P.D. (KHOM) (2017)
Background: Chronic Kidney Disease (CKD) undergoing hemodialysis therapy with a long period of time can reduce quality of life. Objective: This study aims to determine the long-standing relationships with quality of life in hemodialysis patients with chronic kidney disease. Method: The method used is analytical observational with cross sectional approach. This research in the Installation Outpatient hemodialysis clinic and hospital medical record section RAA Soewondo in December 2016. The sample size used is at least 39 samples with simple random sampling technique. Data obtained from the questionnaires World Health Organization Quality of Life (WHOQOL). Result: Data analysis was performed using Spearman's test, obtained the value of correlation between the independent variables (long hemodialis) and dependent variable (quality of life) is very strong (r = -0.922) and a significance value of 0.000 (p <0.05). Conclusion: There is a relationship between duration of hemodialysis with the quality of life of patients with chronic kidney disease in hospitals RAA Soewondo Pati.